Negative Pressure Pulmonary Hemorrhage after Laryngospasm during the Postoperative Period - Han, In Soo (Acute Crit Care, 2018)
Negative pressure pulmonary hemorrhage (NPPH) is an uncommon complication of upper airway obstruction. Severe negative intrathoracic pressure after upper airway obstruction can increase pulmonary capillary mural pressure, which results in mechanical stress on the pulmonary capillaries, causing NPPH. We report a case of acute NPPH caused by laryngospasm in a 25-year-old man during the postoperative period. Causative factors of NPPH include negative pulmonary pressure, allergic rhinitis, smoking, inhaled anesthetics, and positive airway pressure due to coughing. The patient’s symptoms resolved rapidly, within 24 hours, with supportive care.